Comparison of 3 different bone-borne type expansion appliances used in surgically-assisted rapid palatal expansion: A finite element analysis - Koc, Osman; Pamukcu, Hande; Kocabalkan, Azize Atakan (MOSBY-ELSEVIER, 2023)
Introduction: This study aimed to compare the effects of 3 different bone-borne type expansion appliances used in the surgically-assisted rapid palatal expansion (SARPE) by finite element analysis. Methods: Three different miniscrew-supported palatal expansion appliances were modeled. Median and lateral osteotomies were performed without pterygomaxillary suture separation. Model I consisted of a palatal expander with 2 miniscrews placed 4 mm far from the midpalatal suture. In model II, 2 miniscrews were located at the alveolar ridge between the first molar and the second premolar. In model III, 4 miniscrews were placed as a combination of the first and second models. Stress distributions and amount of displacements were evaluated with Ansys software (version 19.2; Ansys, Canonsburg, Pa) for 5-mm expansion in a symmetrical finite element analysis model to reflect the clinical situation. Results: SARPE simulation using miniscrew-assisted maxillary expanders for all models showed a rotation and tipping of the maxilla. The largest displacement was found for the anterior part of the palate in model II and the posterior part in model III. Although a wedge-shaped expansion pattern was observed in all models, this form was more prominent in model II. The highest stress value (0.91 MPa) was measured in model I, and the lowest value (0.004 MPa) was measured in model II for the anterior nasal spine region. The highest stress value (0.51 MPa) was measured in model III, and the lowest value (0.12 MPa) was measured in model II for the posterior nasal spine region. The lowest stress values were measured in model II for all the craniofacial and maxillofacial structures. Conclusions: Among the models, the lowest stress distribution conditions for craniofacial and maxil-lofacial structures were found in model II. The largest displacement was found at the incisors and anterior part of the maxilla for model II. The greatest displacement was found at the posterior region for model III.
Keywords: MAXILLARY EXPANSION; MINI-IMPLANTS; TOOTH-BORNE; EXPANDERS; STABILITY; SKELETAL; ANCHORAGE; Dentistry, Oral Surgery & Medicine